Removal of nitrate and phosphate from aqueous solutions by microalgae - M.H. Sayadi; N. Ahmadpour; M. Fallahi; M.R. Rezaei (Global Journal of Environmental Science and Management)
The aim of this study was to evaluate the ability of microalgae Spirulina platensis and Chlorella vulgaris to remove nitrate and phosphate in aqueous solutions. Spirulina platensis and Chlorella vulgar is microalgae was collected in 1000 ml of municipal water and KNO3, K2HPO4 was added as sources of nitrate and phosphate in three different concentrations (0.25, 0.35 and 0.45g/L). During the growth period, the concentration of nitrate and phosphate was recorded at 1, 4, 6 and 8 days. The highest nitrate removal on the 8 day for Chlorella vulgaris was 89.80% at the treatment of 0.25g/L and for Spirulina platensis was 81.49% at the treatment of 0.25g/L. The highest phosphate removal for Spirulina platensis was 81.49% at the treatment of 0.45g/L and for Chlorella vulgaris was 88% at the treatment of 0.45g/L. The statistical results showed that the amount of phosphate and nitrate removal during different time periods by Chlorella vulgaris depicted a significant difference at P